Declínio da produção de farinha de mandioca: uma análise na visão da comunidade do ramal Cataiandeua Abaetetuba-PA - PALHETA, Mauriléa Muniz (2019)
This paper discusses the decline in cassava flour production: an analysis in the community view of the Cataiandeua branch in the municipality of Abaetetuba-Pa. Being a product much consumed by the Pará, we seek from it to analyze the reason for the decline in the cassava production chain in the Cataiandeua community taking into account the production variables such as planted area, harvested area, production, value of production, deforestation. and income transfer policies. The results show that the value of production in the current year is influenced by the amount produced in previous years, which tends to have a positive impact on deforestation, because the higher the value of production, the greater the amount of area is added to the production process. exerting strong pressure on existing forest areas, and consequently increases the rate of deforestation in later periods. Field research is conducted with a number of seven (7) farmers reporting on planting, production, hard work, etc. The research concludes by considering that there was a drop in flour production, many farmers who produced became buyers, which implies an additional expenditure on family budget and sustainable development. The objective of this work is to identify the factors that contributed to the decrease of cassava flour production in the locality and as specific, to make a socioeconomic, historical and demographic diagnosis about the flour production of Ramal Cataiandeua community; identify the general aspects of production, including technologies and working conditions of farmers in flour production and analyze the factors that are influencing changes in the productive profile of the community.